IMPLEMENTASI PERATURAN DAERAH TENTANG BADAN USAHA MILIK DESA (BUMDes) - Salman Alfarisi; Sujianto Sujianto; Meyzi Heriyanto (Universitas Riau, 2017)
Implementation of Local Regulation About Village Owned Enterprise (BUMDes). The purpose of this study is to find out how the Implementation of Regional Regulation Number 18 Year 2007 About BUMDEs in Kampung Rempak Kecamatan Sabak Auh Siak Regency and any factors that hinder it. The research method used is qualitative descriptive method. The informants in this study are the companion from the sub-district, village head, village secretary, BPD, BUMDes board and some people. Data collection techniques using interviews, observation and documentation. The result of the research shows the implementation of Perda on BUMDes in Kampung Rempak Kecamatan Sabak Auh Siak Regency has not run optimally. BUMDes which is expected to be the motor of the economy in the village has not been able to maximize the potential of the village to develop its business units. Factors that impede the implementation of local regulations on BUMDes are the most prominent is the low competence of the less professional implementers in the management of BUMDes and the participation of the community is still low to contribute to advancing BUMDes.